Natural selection and sequence polymorphism - Hughes, Austin (Henry Stewart Talks, 2007)
Inferring selection from patterns of nucleotide substitution, The Major Histocompatibility Complex as an example of positive selection, Immunodeficiency virus escapes from immune recognition, Purifying selection on Single Nucleotide Polymorphisms
Archived at 2021/02/25